Déconstruire Hegel, un geste phénoménologique? Sur Glas de Jacques Derrida - Baptist, Gabriella (B@belonline, 2020)
The essay proposes a reading of Glas, Jacques Derrida’s 1974 enigmatic text, from a phenomenological perspective; it still awaits to be adequately valorized by scholars. Derrida’s approach to Hegel is in fact ‘blended’, since his essays of the 1960s, by direct and indirect reference to those Hegelian interpretations that characterized the French philosophical panorama in the 20th century, were deeply influenced by the phenomenology’s tradition. Jean-Paul Sartre and Georges Bataille are the privileged interlocutors when the question is, in particular, to face the aporia represented by flowers, which cannot be assimilated by dialectics, neither be reduced to pure and simple rhetorical effects, which are phenomenologically impregnable.